Evaluation of left ventricular systolic function in different subtypes of pediatric acute lymphoblastic leukemia: a case-control study based on two-dimensional speckle tracking - Yang, Yanfeng; Fu, Chunyan; Shi, Kun; Guo, Yonghong; Shi, Peng; Liu, Hanmin; Gu, Ling; Xiong, Ying (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate whether 2D-STI can detect the reduction of left ventricular systolic function in children with ALL earlier than conventional echocardiography, and to explore the differences in left ventricular systolic function changes among children with different clinical risk classifications of ALL.MethodsThis study selected 39 (n = 39) children with non-acute lymphoblastic leukemia who were admitted to our hospital from October 2018 to March 2020 (this constitutes the control group), and 39 children with acute lymphoblastic leukemia. Among the children with acute lymphoblastic leukemia, they were divided into the standard-risk group (n = 13), intermediate-risk group (n = 13), and high-risk group (n = 13) according to the CCLG-ALL2008 protocol. Conventional echocardiography was used to measure left ventricular diameter at end-diastole (LVDd), interventricular septal thickness at end-diastole (IVSTd), left ventricular posterior wall thickness at end-diastole (LVPWd), left ventricular ejection fraction (LVEF), peak flow velocity of early (E) and late (A) diastolic filling, and E/A ratio. Two-dimensional speckle tracking imaging was employed to measure longitudinal strain values for statistical analysis.ResultsThere were no statistically significant differences in LVDd, IVSTd, LVPWd, LVEF, peak E and A flow velocities, and the E/A ratio among the four groups (P > 0.05). The 2D-STI measurement indicators of the control group were not significantly different from those of the standard-risk group (P > 0.05), but showed significant differences compared with the intermediate-risk group and the high-risk group (P < 0.05, P < 0.01); However, among the three groups of children with acute lymphocytic leukemia, except the peak longitudinal strain in the basal segment of the lateral wall, significant differences were observed in the 2D-STI parameters among the groups (P < 0.05).Conclusion2D-STI is superior to conventional echocardiography for the early detection of reduced cardiac systolic function, and the degree of left ventricular systolic function varies among pediatric ALL patients with different clinical risk classifications.